Habitat suitability and niche interaction between invasive snail Achatina Fulica (Giant African Snail) and its biocontrol agent Platydemus Manokwari (New Guinea Flatworm) in Southeast Asia - Yu, Britney Ann.; Edullantes, Brisneve (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Biological invasions are increasingly altering global community structures, especially with the advent of climate change. To regulate their population, researchers introduce biological control agents to invaded areas. Without extensive evaluation, these agents can proliferate, threatening other organisms. This study assessed the niche dynamics between invasive Achatina folic (Giant African Snail) and its biocontrol agent, the Platydemus manokwari (New Guinea flatworm), in the Southeast Asia region. Species occurrence and environmental data were used to model the habitat suitability in the current and future climate scenarios using ecological niche modeling (ENM) with Maximum Entropy (MaxEnt) algorithm. With a moderate predictive accuracy (AUC=0.82 ± 0.1 and AUC = 0.79 ± 0.5), these models predicted 7.44% and 5.64% of the current conditions to be highly suitable for A. fulica and P. manokwari, respectively. Approximately 50% of these areas were predicted to be unsuitable for both species. At the end of the century (2018-2100), A. fulica's highly suitable areas are expected to contract in all future scenarios (SSp126, SSP245, SSP370, and SS9585) to about 99.89% from the current extent. In contrast, these areas will expand for P. manokwari in SSP585 (62.75%) relative to the current conditions. The Schoener's D and Hellinger's I indices reflected a moderate to high niche overlap between the species throughout different climate scenarios ranging from 54.9% to 80.7%. Their niche interaction was stable with minor niche expansion. The niche unwilling by P. manokwari was significant in the current scenarios, SSP126 and SSP245 (p < 0.05). Predicting the suitable areas for invasive species and their niche interaction with other species in future scenarios will aid in identifying vulnerable areas for conservation.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. June 2022.